2023
DOI: 10.1200/jco.22.01015
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose Immunotherapy in Head and Neck Cancer: A Randomized Study

Abstract: PURPOSE The regimens approved for the treatment of advanced head and neck squamous cell carcinoma are accessible to only 1%-3% of patients in low- and middle-income countries because of their cost. In our previous study, metronomic chemotherapy improved survival in this setting. Retrospective data suggest that a low dose of nivolumab may be efficacious. Hence, we aimed to assess whether the addition of low-dose nivolumab to triple metronomic chemotherapy (TMC) improved overall survival (OS). METHODS This was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
62
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(62 citation statements)
references
References 34 publications
0
62
0
Order By: Relevance
“…We have read the recent article published in the Journal of Clinical Oncology by Patil et al, 1 who reported that compared with triple metronomic chemotherapy (TMC, consisting of capsule celecoxib 200 mg twice daily, weekly methotrexate 9 mg/m 2 once a week, and erlotinib 150 mg once daily), the addition of low-dose nivolumab (20 mg flat dose intravenously once every 3 weeks) to TMC (TMC-I) was associated with significantly improved overall survival (OS) in the treatment of advanced head and neck squamous cell carcinoma (HNSCC). The median OS for TMC and TMC-I was 6.7 and 10.1 months, respectively (hazard ratio, 0.545; 95% CI, 0.362 to 0.820; P = .0036).…”
Section: To the Editormentioning
confidence: 99%
“…We have read the recent article published in the Journal of Clinical Oncology by Patil et al, 1 who reported that compared with triple metronomic chemotherapy (TMC, consisting of capsule celecoxib 200 mg twice daily, weekly methotrexate 9 mg/m 2 once a week, and erlotinib 150 mg once daily), the addition of low-dose nivolumab (20 mg flat dose intravenously once every 3 weeks) to TMC (TMC-I) was associated with significantly improved overall survival (OS) in the treatment of advanced head and neck squamous cell carcinoma (HNSCC). The median OS for TMC and TMC-I was 6.7 and 10.1 months, respectively (hazard ratio, 0.545; 95% CI, 0.362 to 0.820; P = .0036).…”
Section: To the Editormentioning
confidence: 99%
“…He suggested strategies such as using lower dose or less frequent dosing (immunotherapy drugs), shorter duration of treatment (6 months of adjuvant trastuzumab instead of 1 year), dose modifiers including food (abiraterone) and therapeutic substitution (use of generics, wherever approved) [ 4 ]. Dr Tannock applauded the conduct of low-dose immunotherapy trials in India (the use of low-dose, 20 mg nivolumab for palliation of head and neck cancer in TMH by Dr Vijay Patil has shown significant improvement in overall survival compared to chemotherapy) [ 5 ].…”
Section: Highlights Of Daymentioning
confidence: 99%
“…In the article that accompanies this editorial, Patil et al 1 reported findings from a randomized clinical trial of nivolumab for advanced head and neck cancer. This trial found a substantial overall survival benefit from the addition of nivolumab to a regimen combining cytotoxic (methotrexate) and targeted (erlotinib) therapies.…”
mentioning
confidence: 99%